Development of Local Wisdom-Based Digital Teaching Materials to Enhance Cultural Literacy and Character: A Needs Analysis - Felia Siska; Yenni Melia; Satrio Junaidi; Abather Rahi Saadoon (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
Digital transformation in education has not been optimally utilized to enhance students’ cultural literacy and character development in junior high school Social Studies (IPS). The limited availability of digital learning materials integrating local wisdom has contributed to weak cultural literacy and insufficient character education. This study aims to analyze the need for developing local wisdom-based digital learning materials to improve students’ cultural literacy and character in Social Studies learning in Sijunjung Regency. Using a Research and Development approach with the Borg and Gall model, data were collected through Focus Group Discussions, questionnaires, interviews, and observations involving 10 Social Studies teachers and 153 students from six junior high schools. The findings indicate that Social Studies learning remains largely textbook-centered, with minimal integration of local culture. While 88% of students show interest in digital-based learning, only 34% are familiar with the Marosok tradition, and 90% of teachers have not used culturally integrated digital materials. These results reveal a gap in cultural literacy and highlight the need for contextual digital learning materials that integrate Social Studies content with local values